The Analysis of Electronic Journal Utilization In Learning Process: Technology Acceptance Model And Information System Success - Achmad Zaky; Muhammad Naufal (LPPM Universitas PGRI Sumatera Barat, 2017)
This study aims to observe the behavior of electronic journal (e-journal) among bachelor students of the Universitas Brawijaya by Technology Acceptance Model (TAM) and Information System Success (ISS) as theoretical framework. The research samples are all bachelor students who have used e-journal in their learning process. The respondents are selected by convenience sampling method. The data are collected through survey and analyzed by Partial Least Square (PLS) with SmartPLS 3. The result of the study reveals that user satisfaction and intention to use have significant effect on actual use of e-journal among bachelor students at the Universitas Brawijaya. Those variables affect the actual use because they have been formed by other variables such as information quality, perceived easiness, perceived usefulness, and attitude towards behavior. Furthermore, information quality has significant influence on user satisfaction, while perceived usefulness and perceived usefulness do not have direct effect on the intention to use. The implication of this study is relevant for educators to recognize the reason factors to use e-journal in the learning process.